Achieving nearly barrier free transport in high mobility ReS2 phototransistors with van der Waals contacts - Shubhrasish Mukherjee; Gaurab Samanta; Md Nur Hasan; Shubhadip Moulick; Ruta Kulkarni; Kenji Watanabe; Takashi Taniguchi; Arumugum Thamizhavel; Debjani Karmakar; Atindra Nath Pal (npj 2D Materials and Applications)
Abstract Focusing on Rhenium disulfide (ReS2), a group VII transition metal di-chalcogenides (TMDC), being a promising contender system for future nanoelectronics and optoelectronics, here, we present an innovative pathway to experimentally achieve an almost barrier-free contact for the ReS2 field effect transistors (FETs) by using few layered graphene as contact electrodes, further supported by comparative first-principles analysis. Such barrier-free contacts enable the observation of metal-to-insulator transition with enhanced room temperature carrier mobility up to 25 cm2/Vs, linear Ids-Vds characteristic down to 80 K, along with the reduction of 1/f noise by more than two orders of magnitude. We further demonstrate a highly responsive gate- tunable phototransistor (R > 106 A/W) at an illumination wavelength of 633 nm. This work demonstrates a straightforward strategy to unlock the full potential of ReS2 for CMOS compatible future electronic and optoelectronic devices.